SENSORIAL QUALITY OF APPLES IN DIFFERENT SYSTEMS PRODUCTION - MARTINS, Carlos Roberto; FARIA, João Carvalho; ROMBALDI, Cesar Valmor; FARIAS, Roseli de Mello (Scientia Agraria, 2010)
The objective was to evaluate the quality sensory of post-harvest apples grown under conventional production systems in transition from conventional-organic, organic and integrated. Cvs apples were harvested. Imperial Gala, Fuji Suprema and Catarina, in commercial orchards in the municipality of São Joaquim / SC in the 2002/03 seasons in four production systems. The fruit were stored in the atmosphere conventional 0 ± 1 ºC and 93 ± 5% RH for 3 months for the ‘Imperial Gala’ and 5 months for the ‘Fuji Suprema’ and ‘Catarina’, followed by 7 days to 15-20 °C. The sensory evaluations were performed at harvest and after of storage. In the joint evaluation of the apples in production systems may arise in a superior visual characteristics of fruit grown in orchards conducted in integrated production systems and organic. In characteristic taste it is superior in fruit grown in organic and integrated system, emphasizing the attributes of acidity, flavor, juiciness and tenderness. The fruits produced in organic and integrated system exhibit superior sensory quality those produced in other production systems.